A guide to prescribing antidepressants in primary care. Issue 8 (13th September 2022) - Woodall, Alan; Walker, Lauren
Abstract : Many newer primary care professionals have limited experience of psychiatry, yet need to manage patients on multiple medications including antidepressants. This article outlines common prescribing dilemmas and solutions for novice primary care prescribers managing patients who require antidepressant therapy.